GAVI : The Global Fund and World Bank Support for Human Resources for Health in Developing Countries - Vujicic, Marko; Weber, Stephanie E.; Nikolic, Irina A.; Atun, Rifat; Kumar, Ranjana (World Bank, Washington, DC, 2013)
Shortages, geographic imbalances, and poor performance of health workers pose major challenges for improving health service delivery in developing countries. In response, development agencies have increasingly recognized the need to invest in Human Resources for Health (HRH) to assist countries in achieving their health system goals. In this paper we analyze the HRH-related activities of three multilateral agencies the Global Alliance for Vaccines and Immunization (GAVI); the global fund for AIDS, Tuberculosis, and Malaria (the global fund); and the World Bank. First, we reviewed the type of HRH-related activities that are eligible for financing within each agency. Second, we reviewed the HRH-related activities that each agency is actually financing. Third, we reviewed the literature to understand the impact that GAVI, the global fund, and the World Bank investments in HRH have had on HRH in developing countries. Our analysis found that by far the most common activity supported across all agencies is short-term, in-service training. There is relatively little investment in expanding pre-service training capacity, despite large health worker shortages in developing countries. We also found that the majority of GAVI and the global fund grants finance health worker remuneration, largely through supplemental allowances, with little information available on how payment rates are determined, how the potential negative consequences are mitigated, and how payments are to be sustained at the end of the grant period. Based on the analysis we argue that there is an opportunity for improved coordination between the three agencies at the country level in supporting HRH-related activities. Existing initiatives, such as the international health partnership and the health systems funding platform, may present viable and timely vehicles for the three agencies to implement this improved coordination.